2003
DOI: 10.1038/sj.ijo.0802486
|View full text |Cite
|
Sign up to set email alerts
|

Overweight Japanese with body mass indexes of 23.0–24.9 have higher risks for obesity-associated disorders: a comparison of Japanese and Mongolians

Abstract: OBJECTIVE:The degree of obesity of Asians is less than that of Caucasians. It has been suggested that Japanese, categorized as having normal weight (BMIo25.0), as defined by WHO (2000), have a tendency toward increased incidences of dyslipidemia and diabetes. Our objective was to analyze parameters constituting obesity-associated disorders in overweight Japanese and Mongolians with a body mass index (BMI) of 23.0-24.9, and to assess the suitability for Asians of the Regional Office for Western Pacific Region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 17 publications
10
102
3
3
Order By: Relevance
“…11?6 % in China cohort) (21) than comparable Western studies (2?2-3?0 % in NHANES), by including many who were not healthy to start with and were vulnerable for onslaught by malnutrition or infectious diseases. The way overweight or obesity was alternatively defined in our study fits the definition proposed by WPRO (16) and Shiwaku et al (19) . By way of mortality (28) or in an industrial cohort (RR 5 0?94 for overweight and RR 5 1?25 for obese group) (33) .…”
Section: Discussionmentioning
confidence: 91%
“…11?6 % in China cohort) (21) than comparable Western studies (2?2-3?0 % in NHANES), by including many who were not healthy to start with and were vulnerable for onslaught by malnutrition or infectious diseases. The way overweight or obesity was alternatively defined in our study fits the definition proposed by WPRO (16) and Shiwaku et al (19) . By way of mortality (28) or in an industrial cohort (RR 5 0?94 for overweight and RR 5 1?25 for obese group) (33) .…”
Section: Discussionmentioning
confidence: 91%
“…In addition, inflammatory processes have recently received a great deal of attention in atherogenesis, and C-reactive protein (CRP) is one of the representative markers 11) . However, there are few comparative studies on atherosclerosis between Mongolian and Japanese populations 5,12) , and there are no such studies examining CAVI and CRP in particular in patients with atherosclerosis-related diseases. Therefore, the objective of the present study was to compare the atherosclerotic traits, including CAVI and CRP, between Mongolian and Japanese patients with HT and DM.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, obese people are increasing in Mongolia, and it was reported that one-third of the diabetic people were obese 4) . It was reported that there were proportionally more people in Mongolia than in Japan who were overweight or had a lot of body fat 5) . Ten years ago, prevention and management of diabetes were first established as important national goals for Mongolians 4) .…”
Section: Introductionmentioning
confidence: 99%